Pengaruh Kepercayaan Pada Atasan, Komitmen Organisasi Dan Kepuasan kerja Terhadap Produktivitas Karyawan (Studi Empiris pada Bagian Umum Di Balai Kota Malang Periode 2018) - Tri Iswandi; Abdul Kodir Djaelani; A. Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
Abstract This study aims to determine and analyze the influence of trust on the boss, organizational commitment and job satisfaction simultaneously and partially to the productivity of employees in the general section of Malang City Hall. Population in this research is employees of City Hall of Malang City general part. The sample in this research using saturated sampling technique amounted to 40 employees. The analysis was done by using panel regression model. The results of this study indicate that trust in the boss partially significant effect on employee productivity with value (sig 0.017), organizational commitment partially significant effect on employe productivity with value (sig .0,040), job satisfaction partially significant effect on employee productivity with value (sig. 0.000). Keywords: trust in superiors, organizational commitment, satisfaction and Productivity employees